POLITIK HUKUM PENGUATAN FUNGSI NEGARA UNTUK KESEJAHTERAAN RAKYAT (Studi Tentang Konsep Dan Praktik Negara Kesejahteraan Menurut UUD 1945) - Riwanto, Agus; Gumbira, Seno Wibowo (Jurnal Hukum dan Peradilan, 2017)
According to the constitution, the state concept in constitutional practice can be divided into two opposite poles, namely welfare and liberal state. They have different characteristics in which the first concept (welfare state) requires a strong and extensive state functions to regulate an economic justice, on the contrary the second concept (liberal state) relies on the free market economy which state’s role should be marginalized. Sosio-legal research is used in this article. Based on the Article 33 of Indonesian post constitutional amendment of 1945, Indonesia embraced the concept of welfare state. Yet, the practice sociologically tends to embrace a liberal state that is not suitable with the welfare of the people. There are challenges, in the context of liberal state, faced by Indonesia, such as applying the capitalist economic system. We may fight the capitalist economic system by two legal policy, namely: first one, we may re-create the role of state functions as a controller and regulator of the economy. The second one, we may increase the state income through taxes along with the higher social spending to achieve the social welfare and economic justice.Keywords: welfare state, the constitution of 1945, legal policy